Characterization of Structural and Physicochemical Properties of an Exopolysaccharide Produced by Enterococcus sp. F2 From Fermented Soya Beans - Jiang, Guangyang; Gan, Longzhan; Li, Xiaoguang; He, Juan; Zhang, Shihao; Chen, Jia; Zhang, Ruoshi; Xu, Zhe; Tian, Yongqiang (Frontiers in Microbiology, 2021)
The present study sought to isolate a novel exopolysaccharide (EPS-F2) from Enterococcus sp. F2 through ethanol precipitation, anion-exchange, and gel-filtration chromatography and characterize the physicochemical properties by spectral techniques. EPS-F2 was identified as a neutral homo-exopolysaccharide composed of only glucose with a high molecular weight of 1.108 × 108 g/mol. It contained →6)-α-D-Glcp-(1→ linkage in the main chain and →3, 6)-α-D-Glcp-(1→ branch chain). Moreover, EPS-F2 possessed excellent thermal stability (266.6°C), water holding capacity (882.5%), oil holding capacity (1867.76%), and emulsifying activity against various edible oils. The steady shear experiments exhibited stable pseudo plasticity under various conditions (concentrations, temperatures, and pHs). The dynamic oscillatory measurements revealed that EPS-F2 showed a liquid-like behavior at a low concentration (2.5%), while a solid-like behavior at high concentrations (3.0 and 3.5%). Overall, these results suggest that EPS-F2 could be a potential alternative source of functional additives and ingredients and be applied in food industries.